Aspectos da modulação da resposta imune induzida na infecção por Plasmodium vivax - Natália Satchiko Hojo de Souza (2016)
Malaria is a disease caused by a protozoa of the genus Plasmodium, accounting for high morbidity rate (besides the cases of mortality especially among children), resulting in serious impact on the socioeconomic development in endemic regions. In Brazil, the main species causing malaria is Plasmodium vivax. Studies involving immune response of patients infected with P. vivax can reveal important aspects for understanding the pathogenesis of disease and provide insight to the development of vaccines and more effective drugs for treatment. Aiming to analyze the immune modulation during P. vivax infection in the present study, the following aspects were investigated: (i) verify the occurrence of apoptosis in CD4+ T cells and the signaling pathways involved; (ii) determine the phenotypic profile of CD8+ T lymphocytes and the possible role of these cells in modulating the immune response; (iii) verify the contribution of T cells as the cellular source of IL-17; (iv) characterize the network of plasma cytokines/chemokines during the acute phase and after-treatment in P. vivax malaria to identify potential biomarkers of active disease. In the study of apoptosis, it was observed that individuals infected with P. vivax showed a higher percentage of CD4+ T lymphocytes in both early apoptosis and late apoptosis. Regarding to apoptosis signaling pathways it was observed an increase in TNFRSF1B and Bid gene expression and reduction in Bcl-2 in CD4+ T cells from infected individuals, suggesting that cell death occurs by extrinsic pathway, with subsequent activation of the intrinsic pathway. The evaluation of CD8+ T lymphocytes demonstrated that individuals infected with P. vivax showed reduced numbers of naïve and memory CD8+ T lymphocytes and reduction in the number of central memory CD8+ T cells. Concerning to cytokine expression, the number of naïve CD8+ T cells expressing IFN-, TNF- and IL-10 was reduced during infection, whereas the number of memory cells expressing TNF- and IL-10 was increased. Positive correlations between the number of cells expressing IFN- or TNF- and the number of cells expressing IL-10 were observed in infected individuals regardless the CD8+ subpopulation, suggesting an immunomodulatory profile. Regarding to T cells it was observed a reduction of these cells during blood-stage of vivax malaria. Furthermore, during infection it was also observed a reduction in TCR+CD27+ subset as well as Th1-like T cells. Another important finding was the absence of Th17-like T lymphocytes in both groups, demonstrating that these cells do not constitute major source of IL-17 during infection. The study of the cytokine/chemokine profiles in P. vivax patients showed higher levels of inflammatory mediators such as IL-6, IL-17, CCL2 and CXCL10, as well as anti-inflammatory/immunomodulators mediators, such as IL-10 and TGF-. Furthermore, reduced levels of the inflammatory cytokine IFN- were observed in infected individuals. The IL-6, IL-10, CCL2, CXCL10 and IFN- levels were restored after antimalarial treatment. Patients with high parasitaemia, as well as, individuals with more than 5 previous malaria episodes, exhibited elevated plasma levels of IL-10. Concerning the analysis of 11-mediators correlation network, a strong positive correlation between IL-6 and CCL2 was revealed, regardless of parasitaemia and number of previous infections. In addition, patients with low parasitaemia showed an association of IL-6/CCL2 axis with IFN-, whereas the association of this axis with IL-10 was observed in patients with high parasitaemia. The different approaches used evidence the occurrence of significant reduction of CD4+, CD8+ and T cells, as well as, modulation of the pro-inflammatory response during P. vivax infection